Media and its Intersections with Workplace Femininities: A Systematic Literature Review - Chamba, Z.N. (NSBM Green University, 2022)
An overarching literature review was performed on studies focused on media and its intersections with workplace femininities published from the year 2010 to 2022. This review systematically selected 16 journal articles on media and its influence on femininities within the workplace. Articles were reviewed based on its methodological choices, context, use of theories, main findings and conclusions, in order to gain a thorough overview of the literature and knowledge in this area of study. Findings of the review revealed that researchers had utilized a variety of methodological stances to conduct their studies. The majority of the studies in the field followed a qualitative approach, and most studies relating to media, organizations/workplace and femininities or gender utilized content or discourse analysis as the research analysis lens to extract and evaluate the data. The qualitative studies in the area were primarily based on gender, feminist and postfeminist theories. Moreover, the review uncovered core rubrics within the main findings of the studies, such as institutional influence, the romanticization of the ‘career woman’ and its aesthetic nuances, the postfeminist ideology which negates the issues of hegemonic structures, and the existence of sexual objectification via the commodification of women’s bodies. Further, significant gaps were identified, pertaining to context and other variable factors of gendered identities, that could be bridged by future studies.
Keywords: Media; Femininities; Organization and Gendered Identities; Workplace Femininities; Gender Representations